Monitoring of the discoloration on γ‐irradiated PE and EVA films to evaluate antioxidant stability. Issue 18 (18th January 2018) - Gaston, Fanny; Dupuy, Nathalie; Marque, Sylvain R. A.; Gigmes, Didier; Dorey, Samuel
ABSTRACT: γ‐Irradiated films could provoke unexpected interaction with proteins for instance just after irradiation and not necessarily after 12 months indicating there is no more reactive species. The optical properties of two multilayer films [polyethylene (PE)/ethylene vinyl alcohol (EVOH)/PE and ethylene vinyl acetate (EVA)/EVOH/EVA] after different γ‐irradiation doses is then studied in this work. The investigation on these films, either non‐irradiated or γ‐irradiated (up to 270 kGy), is performed by colorimetry measurement over time (up to 12 months) to assess the generation of new species inside the materials. The color change is directly correlated with absorbed γ‐doses. Over time, the color decreases and goes back to its initial time level. This discoloration evolution could be therefore used as an indication of the completion of the generated species reactions induced by γ‐irradiation. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46114. Abstract :